IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN IPS DI INDONESIA: SEBUAH SYSTEMATIC REVIEW - Asep Asep; Carolina Sri Athena Barus; Desembra Sohilait (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2024)
The Merdeka Curriculum brings a paradigm of perspective in learning in education. Learning is directed towards the potential and characteristics of the learner. This approach in the curriculum is a form of preparation for the nation's successors to be able to face the real facts in the field. This study aims to examine and analyze social studies learning in the implementation of the Merdeka Curriculum in Indonesia. The method used in this writing is a literature study with a systematic review. Systematic review is used to determine the condition of various research related to social studies learning in the implementation of the Merdeka Curriculum in Indonesia. A total of 31 data taken from the Google Scholar database which has been refined with 4 stages (Identification, Screening, Eligibility, and Included). The results of this writing can be written in several points in planning social studies learning in the independent curriculum, teachers prepare relevant modules and designs to guide students to think critically and contextually, in implementation using relevant models and strategies, in assessment used at the beginning and during the learning process to achieve the goals or competencies of learning, the character of students appears through integration into planning, culture and habits and even teachers as role models, the use of relevant teaching materials and materials to develop social problem solving skills and the use of media in improving quality and increasing active and participatory abilities, in its implementation is constrained by teacher readiness, human resources, and technology use.